Therapeutic Strategies of Acute Uncomplicated Cystitis in Women - Federico L. Marini, Nikolas O. Schneider (Open Journal of Physicians and Surgeons, 2024)
Dysuria along with frequent urination and or urgency are the trademark symptoms of acute uncomplicated cystitis, which is one of the common urinary tract infection (UTI), more prevalent in women. The basic goals of effective therapeutic strategies are targeted towards offering relief of symptoms and eradication of the infection. For empirical first-line treatment, the commonly prescribed antibiotics for uncomplicated cystitis include nitrofurantoin and trimethoprim-sulfamethoxazole which is effective and has favorable safety. Depending on the type of antibiotic used and the status of the patient, the length of therapy is usually between three to seven days. Also, non-pharmacological measures must be added to pharmacological ones to help manage the condition. Increased fluid intake helps in diluting the urine and consequently rinsing out germs from the urinary system. A common over the counter analgesic phenazopyridine is recommended to patients as a way of relieving them from the irritating nature of cruelty burning on urination. Patients usually have recurrences of the disease which can be prevented through measures as the use of contraception that prevents coitus before micturation and proper personal hygiene after micturition. Women with recurrent cystitis may become eligible for long-term antibiotic courses or prophylactic treatment. All things considered, it can be concluded that a combination of treatment methods is the only way out and in this case, supportive care, preventive